Linear quadratic regulator (LQR) speed control for DC motor using MC68HC11 - Che Ku Mohd Faizul, Che Ku Mohd Salleh (2008)
Linear Quadratic Regulator (LQR) control problems have been widely investigated in the literature. The performance measure is a quadratic function composed of state vector and control input. If the linear time-invariant system is controllable, the LQR control law will be obtained via solving the algebraic Riccati equation. The LQR tuning algorithm in microcontroller MC68HC11 is applied to the speed control of servo motor. The performance measure to be minimized contains output error signal and differential control energy. The LQR controller receives error signal only and it doesn’t need to feedback full states. The Q matrix can be determined from the roots of the characteristics equation. Once the poles for the closed-loop system are assigned, the existence criteria of the LQR controller are derived. In the motor control systems, error detector signal are used to provide feedback information on the motor. This error comparator is used in the control loop and to improve the reliability by detecting fault conditions that may damage the motor.